Analisis Jalur Gaya Kepemimpinan, Tingkat Penghargaan dan Kondisi Kerja Terhadap Prestasi Kerja Karyawan Pabrik Karung Rosella Baru PTPN XI (Persero) - Lilis Ardini; Siti Rokhmi Fuadati (Jurnal Manajemen dan Wirausaha, 2009)
Surabaya New Rosella sack factory is one of several player that supply sacks need in Indonesia. With production capacity around 10,2 million sacks per year (beritajatim.com), then there is no problem in marketing its product. Besides fulfill the need of PTPN XI, sacks demands for Bulog, fertilizer factory and rice traders are still high. Therefore, in this research, there will an examination about Human Resources aspect, that is the direct influence of leadership style on working achievement and its indirect influence on appreciation level and working condition. Total sample that used is 20% from production division and common division around 46 persons. Analysis technique that being used is lane analysis to find out direct and indirect influence parameter. The result is that leadership lane directly has no significant influence on working achievement, meanwhile leadership style indirectly through working condition has significant influence on working achievement. Total direct and indirect influence is around 0,221 or 22,1%. The result shows that leadership style is indeed has no significant influence on working achievement of employees of Surabaya New Rosella Sacks Factory. It is caused by the location of raw material, sugar production and its management that located outside the city of Surabaya, meanwhile its package material that is Rosella plastics sacks is located in Surabaya, therefore there is relatif big costs, thus, companys main problem is at its infrastructure that do not support efficient production activities process. The cause is that leadership style has less significant influence on employees working achievement.